An innovation in child health: Globally reaching out to child health professionals. Issue 3 (1st July 2016) - Jones, Russell; Currow, Kathryn; Kwong, Mary; Menon, Pramila
Abstract : Worldwide deaths of children younger than 5 years reduced from 12.7 million in 1990 to 6.3 million in 2013. Much of this decline is attributed to an increase in the knowledge, skills, and abilities of child health professionals. In turn this increase in knowledge, skills, and abilities has been brought about by increased child-health-focused education available to child health professionals. Therefore child-health-focused education must be part of the strategy to eliminate the remaining 6.3 million deaths and to achieve the United Nations Millennium Development Goals. This article describes a child-health-focused program that was established in 1992 and operates in 20 countries: Australia, Bangladesh, Botswana, Cambodia, China, Ethiopia, Hong Kong, India, Kenya, Malawi, Mongolia, Myanmar, Sierra Leone, the Seychelles, the Solomon Islands, Tanzania, Tonga, Vanuatu, Vietnam, and Zimbabwe. The Diploma in Child Health/International Postgraduate Paediatric Certificate (DCH/IPPC) course provides a comprehensive overview of evidence-based current best practice in pediatrics. This includes all subspecialty areas from infectious diseases and emergency medicine through to endocrinology, respiratory medicine, neurology, nutrition, and dietetics. Content is developed and presented by international medical experts in response to global child health needs. Content is provided to students via a combination of learning outcomes, webcasts, lecture notes, personalized study, tutorials, case studies, and clinical practice. One hundred eleven webcasts are provided, and these are updated annually. This article includes a brief discussion of the value and focus of medical education programs; a description of the DCH/IPPC course content, approaches to teaching and learning, course structure and the funding model; the most recent evaluation of the DCH/IPPC course; and recommendations for overcoming the challenges for implementing a multinational child-health-focused program.